Perceptions of coach doping confrontation efficacy and athlete susceptibility to intentional and inadvertent doping - Boardley, I. D.; Smith, A. L.; Ntoumanis, N.; Gucciardi, D. F.; Harris, T. S. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Objectives: We tested a conceptually-grounded model linking athlete perceptions of strength and conditioning and technical coach doping confrontation efficacy (DCE) with athletes` doping self-regulatory efficacy (SRE), doping moral disengagement (MD), and susceptibility to intentional and inadvertent doping. Design: Cross-sectional, correlational. Methods: Participants were high-level athletes (nmale = 532; nfemale = 290) recruited in Australia (n = 261), the UK (n = 300), and the USA (n = 261). All participants completed questionnaires assessing the variables alongside a variant of the randomized response technique to estimate the prevalence of doping. Results: The estimated prevalence of intentional doping in the sample was 13.9%. Structural equation modelling established: (a) perceptions of technical and strength and conditioning coaches` DCE positively predicted doping SRE; (b) doping SRE negatively predicted doping MD; (c) doping MD positively predicted susceptibility to intentional and inadvertent doping; and (d) the predictive effects of coach perceptions on susceptibility to doping were mediated by doping SRE and doping MD. Multisample analyses demonstrated these predictive effects were invariant between males and females and across the three countries represented. Conclusions: The findings show the conceptually-grounded model to offer extended understanding of how multiple individuals within the athlete support personnel network may influence athlete doping.